Pemberdayaan Petani Keramba Jaring Apung di Desa Pematang Jering: Kendala dan Strategi (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the empowerment of floating net cage farmers in Pematang Jering Village and identify the obstacles and strategies implemented by the Village Government in optimizing this empowerment. The method used is descriptive qualitative, with data collection techniques through interviews, observation, and documentation. Research informants included the Village Head, cage farmers, fisheries extension workers, and the Fisheries Service. The results showed that empowerment had covered five indicators of success according to Edi Suharto: economic capacity, active participation, independence, increased knowledge and skills, and social networks. However, the economic capacity and independence of farmers were not yet optimal due to challenges such as high feed prices and limited access to capital. Community participation was high, as reflected in active involvement in village deliberations, training, and group cooperation. The empowerment strategies implemented included capital facilitation, strengthening farmer groups, business management training, and collaboration between the village government, extension workers, and the fisheries service. This study concludes that synergy among local actors is very important in strengthening farmer empowerment, but further strategic steps are needed to increase the independence and sustainability of aquaculture businesses in villages.